نظام الوزارة في مملكة غرناطة في عصر بني نصر635-897هـ/1238-1492م - طويل، أسماء, نسيبي، سناء (جامعة الوادي university of Eloued, 2019)
الملخص: جاءت الدراسة بعنوان نظام الوزارة في مملكة غرناطة في عهد بني نصر(635_897ه/1238_1492م)، فالوزارة عبارة عن كلمة مشتقة من الوزر أي الثقل لأن الوزير يحمل أعباء الحكومة عن الملك، الأزر: الظهر لأن الملك يقوى بوزيره كقوة البدن بظهره، الوزر: الملجأ و المعتصم لأن الملك يلجأ إلى رأيه و معونته. فالوزارة مرتبتها بعد الخلافة، فلذلك يجب اختيار الوزير لدولة أن يكون له أسس وقواعد وآداب خاصة بيه ،ليميزه عن باقية الجمهور. ولقد عالجت دراستنا هذه التساؤل الرئيسي المتمثل في: * كيف كان نظام الوزارة في مملكة غرناطة أثناء فترة حكم بني نصر؟. كما اندرجت تحت هذا التساؤل الرئيسي أسئلة فرعية أهمها: *ما هي أسس لتعيين الوزير في عهد بني نصر؟. *ما هي أهم صلاحيات الوزير و فيما تتجلي ؟. *كيف كان آداب الوزير في عهد بني الأحمر؟. .كيف كانت علاقة الوزير بمن حوله؟. لقد تعددت المناهج في هذه الرسالة ومن أبرزها المنهج التاريخي و المنهج الوصفي و المنهج السردي ،وكما تخلل المنهج المقارن في بعض المباحث و خاصة في المبحث التمهيدي ،وكل هذه المناهج المتبعة من أجل بناء أفكار متناسقة و منسجمة لتسلسل الأحداث التاريخية لوزارة في مملكة غرناطة . كما توصلنا في نهاية دراستنا لمجموعة من النتائج ولعل أبرزها: *إن الوزارة لم تكن وليدة المسلمين سوى في المشرق أو الغرب الإسلامي ،وإنما هي عرفت قبل ظهور الإسلام عند الفرس و الفراعنة القدامى،ولكن عرفت بشكل رسمي و ذو أهمية كبيرة عند العباسيين وفي عهدهم الأول. * تأتي الوزارة بعد الخلافة من حیث الأهمية السیاسیة والإدارية في مملكة غرناطة، والوزیر وسیط بین الخلیفة والرعیة، فھو من ناحیة یُعین الخلیفة في تصریف شئون الدولة ومباشرة مھامه، كما أنھ من ناحیة أخرى یُطلع الخلیفة على أحوال الرعیة بوجه عام. وحسبنا أن الوزیر كان یتقاضى من الدولة راتبا عالیًا ،بالإضافة إلى رواتب تُخصص لأولاده و إخوته، فضلاً عن الضیاع والعقار، والجاه والنفوذ . *يعتبر الحاجب خليفة الملك في بلاطه فلا يستطيع الملك الاستغناء عنه ،فهو يحجب السلطان عن الخاصة و العامة،ويكون واسطة بينه وبين الوزراء فمن دونهم. Résumé : انجلزية The study was entitled The Ministry System in the Kingdom of Granada during the reign of Bani Nasr (635/897 Ah/1238-1492 AD), The ministry is a word derived from the minister, i.e. the weight, because the minister carries the burdens of the government from the king, al-Azar: the back because the king strengthens his minister as the power of the body with his back, the minister and the mu'tasim because the king resorts to his opinion and his aid. The ministry is ranked after the caliphate, so the minister's choice of state must have its own foundations, rules and protocol, to distinguish it from the rest of the public. Our study addressed this key question: How was the ministry system in the Kingdom of Granada during the reign of Beni Nasr? Sub-questions were also included in this main question: What are the grounds for appointing a minister under Bani Nasr? What are the most important powers of the minister and what are they manifested? How was the minister's protocol under The Red Bani? How was the minister's relationship with those around him? There have been many approaches in this letter, most notably the historical approach, descriptive approach and narrative approach, as interspersed with the comparative approach in some detectives, especially in the preliminary research, and all these approaches used in order to build consistent and consistent ideas for the sequence of historical events of the Ministry of Granada. At the end of our study, we also found a set of findings, perhaps the most prominent of which are: The ministry was not born to Muslims except in the East or the Islamic West, but it was known before the advent of Islam among the Persians and ancient Pharaohs, but it was officially known and of great importance to the Abbasids and in their first era. The ministry comes after the succession of political and administrative importance in the Kingdom of Granada, and the minister and the central between the cells and the care, it is from the end of the life of the successor in the conduct of state affairs and directly concerned, and on the other hand it informs the gulf about the conditions of care in general. We calculated that al-Wazer was paid a high salary from the state, in addition to salaries allocated to his children and brothers, as well as property, money and influence. The eyebrow is considered the king's successor in his court, and the king cannot do without him, because he withholds the sultan from private and public, and he is a medium between him and the ministers without them
مذكرة ماستر تاريخ تخصص تاريخ الغرب الإسلامي
Keywords: الوزارة عند المسلمين، الوزارة في الأندلس، غرناطة; Ministère des musulmans, Ministère de l'Andalousie, Grenade; Ministry of Muslims, Ministry of Andalusia, Granada